Eliciting Recovery Narratives in Global Mental Health: Benefits and Potential Harms in Service User Participation - Kaiser, Bonnie N. (Psychiatr Rehabil J, 2019)
OBJECTIVE: The engagement of peers and service users is increasingly emphasized in mental health clinical, educational, and research activities. A core means of engagement is via the sharing of recovery narratives, through which service users present their personal history of moving from psychiatric disability to recovery. We critically examine the range of contexts and purposes for which recovery narratives are elicited in global mental health. METHODS: We present four case studies that represent the variability in recovery narrative elicitation, purpose, and geography: a mental health Gap Action Programme clinician training program in Nepal, an inpatient clinical service in Indian-controlled Kashmir, a recovery-oriented care program in urban Australia, and an undergraduate education program in the rural United States. In each case study, we explore the context, purpose, process of elicitation, content, and implications of incorporating recovery narratives. RESULTS: Within each context, organizations engaging service users had a specific intention of what ‘recovery’ should constitute. This was influenced by the anticipated audience for the recovery stories. These expectations influenced the types of service users included, narrative content, and training provided for service users to prepare and share narratives. Our cases illustrate the benefit of these co-constructed narratives and potential negative impacts on service users in some contexts, especially when used as a prerequisite for accessing or being discharged from clinical care. CONCLUSIONS AND IMPLICATIONS FOR PRACTICE: Recovery narratives have the potential to be used productively across purposes and contexts when there is adequate identification of and responses to potential risks and challenges.